Kissing interactions for the design of a multicolour fluorescence anisotropy chiral aptasensor - Chovelon, Benoit; Fiore, Emmanuelle; Faure, Patrice; Peyrin, Eric; Ravelet, Corinne (Talanta (Oxford), 2019)
The development of enantioselective assays and sensors has received much attention for the determination of enantiomeric impurities. Herein, we demonstrated that the previously reported aptamer kissing complex (AKC) assay strategy can be implemented for designing a chiral tool that allows both the simultaneous enantiomer quantification and the enantiopurity analysis. D- and L-arginine vasopressin (AVP) were employed as model enantiomeric targets. The D- and L-AVP engineered aptamers (aptaswitch) were used as recognition units whereas the Fluorescein or Texas Red labelled D- and L-hairpin probes (aptakiss) served as probes of the enantiomer-dependent AKC formation. The orthogonal fluorescence anisotropy signaling scheme at two different emission wavelengths permitted the concomitant sensing of the AVP enantiomers in a single sample, under a high-throughput microplate format. It was also shown that the AKC-based enantioselective sensor allowed the enantiomeric impurity detection at a level as low as 0.01%. [Display omitted] •A orthogonal fluorescence anisotropy chiral aptasensor was reported.•The enantioselective assay principle was based on the aptamer kissing complex strategy.•The aptasensor provided the concomitant detection of oligopeptide enantiomers in the same sample.•An enantiomeric impurity of as low as 0.01% was detected in a non racemic mixture.